Gaya Bahasa Dakwah Gus Miftah di Pasar Kembang Yogyakarta: Analisis Isi Akun YouTube @GusMiftahOfficial - Siti Mariyam (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2024)
This research examines in depth the preaching of Gus Miftah at Pasar Kembang Yogyakarta by highlighting two main problems, namely the message of preaching and the language style of Gus Miftah's preaching. This research uses a descriptive qualitative approach with content analysis research type. Content analysis is a research tool that concentrates on actual content and media characteristics, in this case the preaching content of Gus Miftah @GusMiftahOfficial episode "Sarkem Workers Ask to Be Converted to Gus Miftah, Mashallah!!! Latest Gus Miftah 2024â€. The data analysis stage uses the analysis techniques proposed by Milles and Huberman starting from reducing data, presenting data, and making conclusions. The results of research on Gus Miftah's preaching at Pasar Kembang Yogyakarta show: First, Gus Miftah conveyed preaching messages that were relevant to the daily lives of women night workers, such as patience, tawakkal, social concern, courage in doing good deeds, and guarding against disgrace. Gus Miftah also conveyed messages from practical, physical, and health aspects. Second, Gus Miftah's preaching language style has several characteristics that make it effective in conveying preaching messages to female night workers at Pasar Kembang Yogyakarta, namely, light and easy to understand language, emphasis on reason and logic, and a humorous language style. Gus Miftah succeeded in creating a space for dialogue that was more open, less rigid, and seemed to be in harmony with his mad'u.